The Influence of Investment Decisions, Profitability, and Company Size on Company Value - Sari, Ika; Matsani; Safitri, Devi (Gorontalo Accounting Journal, 2026)
The purpose of this study is to examine the influence of investment decisions, profitability, and company size on company value in banking subsector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2024. This study uses a quantitative method with a causal approach and purposive sampling. The data used are secondary data and were analyzed using multiple linear regression using SPSS 26. The results of this study indicate that investment decisions and company size do not affect company value while profitability affects company value.